SAMUEL DUCLOS’ CRITIQUE OF ROBERT BOYLE’S CORPUSCULAR PHILOSOPHY: A CONTROVERSY ABOUT THE CONCEPT OF ‘CHEMISTRY‘ - Kucharski, Dariusz (Studia Philosophiae Christianae, 2020)
The seventeenth century witnessed the transition from qualitative to quantitative physics. The very process was not easy and obvious and it consisted of discussions in many fields. One of them was the question about the nature of chemistry which was at the time undergoing some changes towards the form we know now. The main argument concerned the explanatory principles one should invoke to understand properly certain outcomes of chemical experiments. The present paper is a presentation of such an (indirect) argument between R. Boyle, a prominent proponent of corpuscular, quantitative principles and S. Duclos, an al-chymist and a proponent of paracelsian, qualitative ones. What is interesting, Duclos knew The Sceptical Chymist, Boyle’s main work which contained a severe critique of paracelsian chemistry, and a%empted to point out some weaknesses of Boyle’s own position. Duclos scrutinized Boyle’s experiments described in his Certain Physiological Essays and other works and argued for certain shortcomings of Boyle’s laboratory skills, his failure to indicate some literature sources and, first of all, insufficiency of Boyle’s arguments for the corpuscular thesis. According to Duclos, Boyle did not follow in laboratory certain procedures recommended by himself, using unclear notions and applying the corpuscular principles without proper justification. What is more, Duclos argued also in favour of paracelsian chymistry presenting some qualitative explanations in experiments in which Boyle failed to give quantitative ones. Knowing the further development of natural philosophy, it seems interesting to realize how complex it was. The present paper shows also how much irremovable from scientific research is the theoretical component.